The Effect of Accounting Knowledge and Education Level on MSME Performance with the Application of Accounting Information Systems and Understanding of SAK EMKM as Intervening Variables - Robiur Rahmat Putra; Syaka Nur Khalisa (Politeknik Ganesha Medan, 2023)
This research uses accounting information systems and an understanding of SAK EMKM as intervening factors to evaluate and assess the impact of accounting knowledge and education level on the performance of MSMEs. 189 SMEs from the neighborhood of DKI Jakarta, particularly North Jakarta, made up the sample for this research. Hair's plan held that there were enough respondents. By uploading study questionnaires as Google forms and delivering them to MSME participants through social media, the data gathering strategy used simple random selection. The Smart PLS (Partial Least Square) software is employed in this study's data processing technique to evaluate the hypothesis. The findings of this research suggest that MSME actors should learn accounting in order to use accounting information systems to their business continuity in order to enhance their performance.